Blockchain Technology Applications for Decarbonization: A Bibliometric Review - Kalnina Anete; Feofilovs Maksims; Romagnoli Francesco (Environmental and Climate Technologies, 2025)
The integration of decentralized and digital technologies like blockchain in sectors that aim to fulfil certain decarbonization goals could be a promising solution to facilitate the transition to climate neutrality. With the aim to construct a comprehensive and systematic bibliometric analysis on the inclusion of blockchain technology in renewable energy, transport (electric vehicles) and agri-food industry, this paper provides an in-depth analysis of existing studies on these topics to identify future research opportunities. Using R-studio, Web of Science and Scopus data were analysed and visualized. The results of this study indicate growth of the publication count throughout the years. This research shows that the most productive countries are China and India, although the average citations per article is higher in United States of America and United Kingdom. Trend topics, thematic evaluation and co-occurrence network from this study suggest that the application of blockchain technology in analysed sectors should be combined with other digital solutions like Internet of Things and artificial intelligence to increase security, facilitate systems’ management and assist in policy planning. The identified research gaps are connected to blockchain technology and renewable energy storage systems (e.g., hydrogen), materials used in electric vehicles’ batteries and circularity (including life cycle and recycling) in the agri-food sector and other studied sectors.